1988
DOI: 10.1002/ptr.2650020205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacosides A and B on avoidance responses in rats

Abstract: The nerve tonic activity of Bacopa monniera has been attributed to two saponins named Bacosides A and B. In the present investigation, Bacosides A and a mixture of the two saponins were used as aqueous suspensions. In the shock motivated brightness discrimination reaction a single oral dose of 10 mg/kg, 90 min prior to training, significantly reduced the time per trial, increased the number of positive responses and enhanced the relearning index. Similar effects were also observed in the relearning trial, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
104
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 14 publications
2
104
0
Order By: Relevance
“…Recent pharmacological studies indeed confirmed the activity of brahmi as described in Ayurvedic medicines (Singh et al, 1988). It was also confirmed that the activity was due to the saponins present in the alcoholic extract of the plant (Chakravarty et al, 2001).…”
Section: Pharmacological Studiesmentioning
confidence: 55%
See 1 more Smart Citation
“…Recent pharmacological studies indeed confirmed the activity of brahmi as described in Ayurvedic medicines (Singh et al, 1988). It was also confirmed that the activity was due to the saponins present in the alcoholic extract of the plant (Chakravarty et al, 2001).…”
Section: Pharmacological Studiesmentioning
confidence: 55%
“…Several pharmacological (Singh et al, 1988(Singh et al, , 1997) and clinical studies (Nathan et al, 2001 andStough et al, 2001) on the extracts of B. monnieri standardized to the bacosides A and B have been published. B. monnieri extracts are widely available with label claims on the content of bacosides A and B in the international nutraceutical market.…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…Further investigation on the extract led to the isolation of four phenylethanoid glycosides, of which the three new compounds have been designated as monnierasides I-III (1-3). The fourth one has been proved to be identical with plantainoside B 13) (4). The present paper reports the isolation and structure elucidation of three new glycosides (1-3).…”
mentioning
confidence: 76%
“…1) Recent pharmacological studies indeed confirmed the activity. [2][3][4] It was also confirmed that the activity was due to the glycosides present in the alcoholic extract of the plant. Because of the presence of a large number of glycosidic constituents in the extract as an intimate mixture, two groups of workers could isolate and characterize only a part of the constituents.…”
mentioning
confidence: 85%
“…Bacoside rich extract from Bacopa monniera was prepared from the standard procedure (Singh et al 1988). The amount of bacosides present is quantified by using a Jasco LCNetII/ADC HPLC system equipped with a HiQ Sil C18HS (150×4.6 mm, 5 μm particle size) column, photodiode array detector (PDA), an PU 1580 pump (Jasco, USA) and a Rheodyne injector with 20 μL loop.…”
Section: Isolation and Estimation Of Bacosidementioning
confidence: 99%